Akuntabilitas Dan Transparansi Dalam Tata Kelola Anggaran Pendapatan Dan Belanja Daerah (Apbd): Kajian Atas Praktik Di Kota Pekanbaru Tahun 2025 - Muhammad Agung Robani (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study evaluates the extent to which accountability and transparency principles are embedded in the budget management cycle of Pekanbaru City's Regional Revenue and Expenditure Budget (APBD) during the 2025 fiscal year. Both principles constitute fundamental pillars in achieving quality, clean, and public-oriented governance. The research adopts a descriptive-analytic qualitative framework, integrating three data collection methods: intensive interviews with key stakeholders, direct observation of financial administration processes, and in-depth review of official budget documents and financial reports. Data analysis follows the condensation, presentation, and conclusion-drawing procedures conceptualized by Miles, Huberman, and Saldana. Findings reveal that Pekanbaru City Government has established and operationalized several accountability and transparency instruments, including electronic budgeting (e-budgeting), digital platforms for public financial information, and periodic reporting mechanisms to supervisory bodies. Nevertheless, fundamental challenges persist, such as digital competency gaps among financial managers, data fragmentation across government work units, and limited citizen engagement in budget monitoring. The study concludes that an integrated reform agenda targeting regulatory strengthening, system modernization, capacity building, and public participation mobilization is urgently needed as a strategic priority for improving Pekanbaru's regional financial governance.